INHIBITORY ACTIVITY OF COBALT(II)–MORIN COMPLEX AGAINST THE REPLICATION OF DENGUE VIRUS TYPE 2 - Sucipto, Teguh Hari; Churrotin, Siti; Setyawati, Harsasi Setyawati; Mulyatno, Kris Cahyo; Amarullah, Ilham Harlan; Ueda, Shuhai; Kotaki, Tomohiro; Sumarsih, Sri; Wardhani, Puspa; Bendryman, Sri Subekti; Aryati, Aryati; Soegijanto, Soegeng; Kameoka, Masanori (Institute of Topical Disease Universitas Airlangga, 2017)
Dengue virus (DENV) is a significant pathogen emerging worldwide as a cause of infectious disease. Antidengue treatments are urgently required to control the emergence of dengue. DENV is a mosquito-borne disease responsible for acute systemic diseases and serious health conditions. DENVs were distributed in the tropical and sub-tropical areas and transmitted to humans by Aedes agypty and Aedes albopictus. Dengue vaccine or antiviral has not yet been clinically approved for humans, even though there have been great efforts toward this end. Antiviral activity against DENV is an important alternative for the characterization and development of drugs. Metal–organic compounds were reported to exhibit fungicidal, bactericidal, and antiviral activities its inhibitory activity was not significant, at high concentration it was more toxic to replicating cells than to stationary cell monolayers of Vero cells. The aim of this study is to investigate the antiviral effects of Cobalt(II)–Morin complex. This compound was further investigated for its inhibitory effect on the replication of DENV-2 in Vero cells. The replication of DENV was measured by enzyme-linked immunosorbent assay and the value of selectivity index (SI). SI was determined as the ratio of the 50% cytotoxic concentration (CC50) to the 50% inhibitory concentration (IC50). The IC50 value of the Cobalt(II)–Morin complex for DENV-2 was 3.08 µg/ml, and the CC50 value of the complex for Vero cells was 3.36 µg/ml; thus, the SI value was 1.09. The results of this study demonstrate the antidengue serotype 2 inhibitory activity of Cobalt(II)–Morin complex and its high toxicity in Vero cells. Further studies are not required before Co(II)–Morin can be applied in the treatment of DENV-2 infections.